A visual analytics approach for exploration of high-dimensional time series based on Neighbor-Joining Tree - Rodríguez R. (2018)
The authors would like to thank CONCYTEC (Consejo Nacional de Ciencia, Tecnología e Innovacíón Tecnológica), FONDECYT (Fondo Nacional de Desarrollo Científico y Tecnológico) and UNSA (Universidad Nacional SanAgustín) of Perú.